Cattle ranchers, colonists and deforestation of primary forests in Morona, Ecuador - Bedoya Garland, Eduardo (2023)
The objective of this article is to describe and analyze the productive characteristics and the corresponding environmental impact of the small and medium extensive cattle ranching practiced by colonists-mestizos and settlers belonging to the Shuar ethnic group in the Morona canton, located in the Ecuadorian Amazon. It is undisputable that there are forms of extensive livestock farming that are more sustainable than others, but we believe that the volume of land cleared is a problem that must be addressed. This production system is based on the movement of cattle between pastures on a farm due, among other things, to the low nutritional potential of the gramalote grass. This activity generates deforestation in large extensions of land. Among the factors that accentuate such levels of deforestation are, on the one hand, the larger size of the agricultural units and the need to compensate for the loss in the nutritional potential of the pastures and, onthe other hand, the chrematistic perception of the forests. Extensive livestockfarming, especially among the colonists, has shown a great capacity for resilience over the last forty years. This is despite fluctuations in urbandemand for meat and its environmental impact on the forest. Cattle ranchers in the region have maintained cattle ranching as an important source of income, a capitalization mechanism, a viable activity in a context of relative labor scarcity, and as a means of obtaining social status in a frontier context. In short, as a way of reproducing their family economy.